2011
DOI: 10.1186/1471-2407-11-359
|View full text |Cite
|
Sign up to set email alerts
|

A novel transferrin receptor-targeted hybrid peptide disintegrates cancer cell membrane to induce rapid killing of cancer cells

Abstract: BackgroundTransferrin receptor (TfR) is a cell membrane-associated glycoprotein involved in the cellular uptake of iron and the regulation of cell growth. Recent studies have shown the elevated expression levels of TfR on cancer cells compared with normal cells. The elevated expression levels of this receptor in malignancies, which is the accessible extracellular protein, can be a fascinating target for the treatment of cancer. We have recently designed novel type of immunotoxin, termed "hybrid peptide", which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 46 publications
2
43
1
Order By: Relevance
“…TfR1 resides on cell membranes and imports cargo by receptormediated endocytosis via clathrin-coated pits. [ 4,8 ] Both SKBR3 and MDA-MB-231 cells possess high levels of TfR1 [ 33 ] which would assist cellular uptake of H-AFt-encapsulated-Gefi tinib. [ 34 ] The greater SKBR3 growth inhibition by H-AFt compared to MDA-MB-231 implies greater sequestration of H-AFt by SKBR3 cells.…”
Section: Communicationmentioning
confidence: 99%
“…TfR1 resides on cell membranes and imports cargo by receptormediated endocytosis via clathrin-coated pits. [ 4,8 ] Both SKBR3 and MDA-MB-231 cells possess high levels of TfR1 [ 33 ] which would assist cellular uptake of H-AFt-encapsulated-Gefi tinib. [ 34 ] The greater SKBR3 growth inhibition by H-AFt compared to MDA-MB-231 implies greater sequestration of H-AFt by SKBR3 cells.…”
Section: Communicationmentioning
confidence: 99%
“…It has previously been reported that agents that modulate iron metabolism in cancer cells, particularly those that restrict iron availability, including iron chelating agents (14,15) and transferrin receptor-targeted treatments (16), exhibit potent and broad anti-tumor activity. Several studies have demonstrated that the mechanism of the anti-tumor action of iron chelators is linked to the inhibition of DNA synthesis, the induction of DNA damage, G 1 -S phase cell cycle arrest, and the activation of apoptosis (15,17); however, research on targeting iron metabolism in cancer cells for anti-tumor therapy is still in its infancy (15).…”
Section: Modulation Of Intracellular Iron Metabolism By Iron Chelatiomentioning
confidence: 99%
“…Cell viability assay was done as described previously (15). Briefly, cells were seeded in 96-well plates at 3 Â 10 3 cells per well and incubated for 24 hours.…”
Section: Cell Viability Assaymentioning
confidence: 99%